Evaluasi Non-Physical Waste Pada Proyek Pembangunan Gedung Rumah Sakit X Dengan Penerapan Lean Construction - Danureswara, Rasendriya Rizki; Suripto (Indonesian Society of Applied Science, 2025)
In construction projects, waste encompasses not only material waste (physical waste) but also includes non-value-added activities such as rework, waiting time, and delays (non-physical waste). Construction practitioners often focus on physical waste, neglecting the importance of non-physical waste, which is a critical issue that deserves attention and effective solutions. Therefore, efforts are necessary to minimize non-physical waste by implementing lean construction methods. This study aims to identify critical non-physical waste and its causes, providing recommendations for preventing them through lean construction. The research involved observations, questionnaires, and interviews, with data analyzed using the Borda method. The findings revealed that the critical non-physical waste in the RS X project was waiting, with a weight of 0.204, primarily due to slow approvals, followed by defects with a weight of 0.180, caused by inadequate supervision. To address waiting, it is recommended to apply the Lean principles of Specify Value and Value Stream Mapping, along with tools like the Last Planner System and Daily Huddle Meetings. For defects, the Value Stream Mapping and Flow approaches, supported by tools such as Fail-Safe for Quality and First-Run Studies, are suggested. While not yet fully optimized, the use of lean construction tools positively impacts the reduction of non-physical waste, thereby enhancing project efficiency and quality.